The use of wordless picture book to stimulate EFL students’ oral descriptive text production in speaking class: a case study at junior high school in Ciamis - Fadilah, Muhamad Rizky; Said, Iskhak; Febriani, R. Bunga (Journal of English Education Program (JEEP), 2024)
This research discusses the use of Wordless Picture Books to stimulate EFL students’ oral descriptive text production in speaking class. Particularly, the purpose of this study was to find out students' perceptions of using Wordless Picture Books to stimulate EFL students’ oral descriptive text production in speaking class. This qualitative case study was conducted in one of the Junior high schools in Ciamis, involving 15 students. Likert scale questionnaires were used to gather the data. The results of this study showed that students responded positively to the use of Wordless Picture Books to stimulate their oral descriptive text. Most of them agree that a Wordless Picture Book for learning descriptive text makes the process more enjoyable, easy, and fascinating. Wordless Picture Books can help students relax, confident and reduce anxiety. For the other researchers, it is suggested to conduct research concerning the implementation of using Wordless Picture Books in teaching other skills, such as teaching writing, teaching reading, etc. In addition, it is recommended that further research concern the use of Wordless Picture Book in descriptive text, by different approach, skills, and ways which was used in the present study.